2021
DOI: 10.1136/heartjnl-2020-318153
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and cardiovascular mortality in 63 million adults from Brazil

Abstract: BackgroundIt has been suggested that cardiovascular disease exhibits a ‘social cross-over’, from greater risk in higher socioeconomic groups to lower socioeconomic groups, on economic development, but robust evidence is lacking. We used standardised data to compare the social inequalities in cardiovascular mortality across states at varying levels of economic development in Brazil.MethodsWe used national census and mortality data from 2010. We used age-adjusted multilevel Poisson regression to estimate the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Cardiovascular disease (CVD), the leading cause of death worldwide, is largely attributable to biological risk factors, such as high systolic blood pressure and high fasting plasma glucose, being overweight or obese and having an inadequate diet, that are disproportionally concentrated amongst poor individuals and those living in LMICs. 14 , 15 In addition to behavioural factors and co-morbidities, premature mortality (i.e. death among persons aged 30–69 years) 16 from CVD and all causes are strongly and consistently associated with low socio-economic status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease (CVD), the leading cause of death worldwide, is largely attributable to biological risk factors, such as high systolic blood pressure and high fasting plasma glucose, being overweight or obese and having an inadequate diet, that are disproportionally concentrated amongst poor individuals and those living in LMICs. 14 , 15 In addition to behavioural factors and co-morbidities, premature mortality (i.e. death among persons aged 30–69 years) 16 from CVD and all causes are strongly and consistently associated with low socio-economic status.…”
Section: Introductionmentioning
confidence: 99%
“…death among persons aged 30–69 years) 16 from CVD and all causes are strongly and consistently associated with low socio-economic status. 14 , 17 Premature mortality is one of the Sustainable Developmental Goals indicators for monitoring effective policies for disease prevention and control. 18 , 19 Therefore, policies aiming to reduce inequalities in CVD risk factors have great potential to reduce related deaths among the most disadvantaged populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that economic development of low-and-middleincome countries might result in worsening CVD risk in higher, compared with lower, socioeconomic (SES) groups, convincing data to support this view is lacking. In this issue of Heart, Mallinson and colleagues 4 used national census and mortality data for Brazil to address this issue. Age-adjusted mortality rates for both women and men with <8 years of education (compared with 8 or more years) was higher in the least, compared with the most, developed states with a similar pattern seen for subtypes of CVD (figure 3).…”
Section: Heartbeatmentioning
confidence: 99%
“…In the field of health, inequalities can be seen in the underprivileged population's limited access to health services 6,7 , as well as in a poorer ratio of doctors by population in poorer towns 7 . These differences in accessibility to health services contribute to higher rates of morbidity and mortality in the black [8][9][10][11] and poorest populations 12 , as became evident during the COVID-19 epidemic 8,10,13,14 .…”
Section: Introductionmentioning
confidence: 99%